Consumers’ purchasing intention towards organic rice - Johari, Nursaadah (2018)
The purpose of this study is to determine the consumers‟ purchasing intention towards organic rice. The emphasis is more towards the relationship between socio-demographic and the factors that influence the consumers‟ purchasing intention towards organic rice. The totals of 400 respondents were chosen using simple random sampling method from selected Klang Valley area. Data that were collected from the survey were analysed using three types of method which were descriptive analysis, factor analysis and chi-square analysis. Factor analysis was conducted to identify the factors that influence consumers‟ purchasing intention towards organic rice. In this study, three (3) factors were identified which are attitude, subjective norms and perceived behaviour control. Chi-square was conducted to identify the relationship between socio-demographic and consumers‟ purchasing intention towards organic rice. The results showed that different age group and educational level have different purchasing intention towards organic rice. From the results, it can be recommended that the producers and marketers of organic rice can do a campaign to promote and sell their products to people that from 26-35 years old and from degree level of education which is during exhibitions and events organized by the university or college, especially events that involve healthy lifestyle such as World Health Day.